Simulation of colloidal suspension systems - Fang, Hongfei (Curtin University, 2010)
The research work is focused on the development of a simulation platform for colloidal suspension. Based on discrete element method (DEM), the model developed takes into account the crucial interactions, i.e. the electrostatic repulsion, van der Waals attraction, Brownian force, hydration effects and hydrodynamic force. The mechanism of colloid particle diffusion in confined space and the combined influences of fluid flow field, geometrical confinement, and the interparticle interactions on the self-assembly process are investigated.